2010
DOI: 10.1097/iop.0b013e3181b80c30
|View full text |Cite
|
Sign up to set email alerts
|

The Bioceramic Implant: Evaluation of Implant Exposures in 419 Implants

Abstract: Implant exposures can occur anytime postimplant placement. This review discovered an implant exposure rate of 9.1%, with the majority of the exposures occurring after the postoperative follow-up period. Patients with porous orbital implants should be followed on a long-term basis to detect this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…3,9 S-100, a marker for differentiated neural tissue and commonly used to diagnose melanoma, has been reported to stain negatively or to have variable expression in neurothekeoma. 2,10 In the present case, there was weak S-100 positivity. CD34 is more commonly negative in neurothekeoma.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…3,9 S-100, a marker for differentiated neural tissue and commonly used to diagnose melanoma, has been reported to stain negatively or to have variable expression in neurothekeoma. 2,10 In the present case, there was weak S-100 positivity. CD34 is more commonly negative in neurothekeoma.…”
Section: Discussionmentioning
confidence: 70%
“…Cellular neurothekeoma is uncommonly found in the periocular area, and the authors are aware of only 5 reported cases involving the eyelid, all of which were noted to have external or unspecified manifestations of the neoplasm. [2][3][4] The current case of cellular neurothekeoma of the eyelid is unique, in that its presentation was completely internal, without any externally detectable eyelid lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a potential complication would be reported and the patient would be referred back. Jordan et al (2010) reported that in a series of 419 cases, surgical technique and previous interventions such as treatment with corticosteroids or radiotherapy were related with implant exposure between 3 and 12 months. Irradiated sockets can have a decreased vascularity and are therefore more prone to implant exposure.…”
Section: Discussionmentioning
confidence: 99%